Buckling characteristic of C-column / Mohd Najib Tugiman and Rusi Muhd Fakhruddin - Tugiman, Mohd Najib; Muhd Fakhruddin, Rusi (2001)
In the first case, stresses exceed the given safe limits resulting in the formation of cracks that cause failure. In the second case, the stresses need not cross the safe values but the structure does not fail physically but it may deform to some other shape (due to external disturbances), which are not tolerable. For most thin-walled structural members loss of stability is in the elastic range, which slightly thick bodies inelastic stability investigations may be needed. Also, load on the structure could be tensile and/or compressive. The loss of stability due to tensile loads falls in the broad category of material instability, whereas the stability under compressive load is usually termed structural (or geometrical or form) instability, commonly known as 'Buckling'. When a slender member is subjected to an axial compressive load, it may not so fail by a buckling condition. Buckling is not so much a failure of material (as is yielding and fracture) but an instability caused by system geometry.